Cancer Patients, Anamnesis, Organon of Medicine, Miasms, Hahnemann, Problems, their Solutions & Strategies? (Advancements in Homeopathic Research, 2022)
This I am writing after treating more than 50,000 (fifty thousand) cases of CANCER of various types and at different stages. Each cancer condition is having its own signs and symptoms as well as each cancer patient is having his / her own sings and symptoms. There were / are cases curable, incurable, incurability and terminal. Cancer a malignant disease, ulceration or growth with cells that have lost their normal control mechanism and thus have unregulated growth.Cancer can develop in any tissue within any organ or system. Resent studies of cancer say that it is based on hereditary, i.e; the passing of physical or mental characteristics genetically from one generation to another (Oxford Dictionary). Please do remember that once a CANCER patient is always a cancer patient through out his/her life.There are every chance to / for reoccurrence due to several factors such as junk food, alcohol, smoking, tobacco chewing, genes, may be bad luck etc; but mainly dissimilar treatment and suppressive (1, Para. 42) and if the patient is not treated miasmatically by a Homoeopath (1, footnote to para 205). The word ‘CANCER’ from the Doctor’s mouth is sufficient on many occasions to bring about the death of a patient inch by inch. Fear of having cancer is the greatest killer of a patient. Fear of cancer is one of the obstacles to overcome in sickness and the greatest hindrance to recovery. Fear is followed by depression as long as the suffering continues with cancer for loosing job, economy, family,friends and finally the World he/she is enjoying.
Keywords: Cancer Patients; Anamnesis; Miasms; Organon of Medicine; Hahnemann